Synthesis of mullite in the presence of nanodisperse aluminum powder - Vereshchagin (Vereschagin, Vereshagin) V. I. Vladimir Ivanovich (2005, 2005)
Synthesis of mullite from a mixture of α-Al2O3 + β-SiO2 and native kaolin-based materials in the presence of nanodisperse aluminum is reported. In both cases, addition of nanodisperse Al increases the yield of mullite and stabilizes its structure